2020
DOI: 10.1111/apt.15650
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: gastric microbiota in health and disease

Abstract: Background Helicobacter pylori is the most infamous constituent of the gastric microbiota and its presence is the strongest risk factor for gastric cancer and other gastroduodenal diseases. Although historically the healthy stomach was considered a sterile organ, we now know it is colonised with a complex microbiota. However, its role in health and disease is not well understood. Aim To systematically explore the literature on the gastric microbiota in health and disease as well as the gut microbiota after bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
119
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 113 publications
(323 reference statements)
8
119
0
3
Order By: Relevance
“…Helicobacter pylori (H. pylori) is a helix-shaped, Gram-negative, microaerophilic, flagellated bacterium that is capable of biofilm formation and converting from spiral to coccoid form [1][2][3][4][5][6]. It is a highly invasive microorganism responsible for one of the highest prevalences of chronic infections worldwide, even though over 80% of infected patients remain asymptomatic [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a helix-shaped, Gram-negative, microaerophilic, flagellated bacterium that is capable of biofilm formation and converting from spiral to coccoid form [1][2][3][4][5][6]. It is a highly invasive microorganism responsible for one of the highest prevalences of chronic infections worldwide, even though over 80% of infected patients remain asymptomatic [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…H pylori manipulates gastric milieu making this niche favorable for some microbial members while unfavorable for others with a global trend towards carcinogenesis. For example, commensal oral and intestinal bacteria are likely to benefit from these alterations as previous studies reported that gastric cancer microbiota was enriched with oral or intestinal taxa 8,10,11 . Interestingly, one study found apparent differences in the composition of microbiota between gastric aspirates and biopsies 6 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 99%
“…Individuals with abundant H pylori in the stomach contain distinct intestinal communities compared with H pylori‐ negative counterparts, indicating an interplay between two gastrointestinal segments 10 . Although precise underlying mechanisms are still scarce, possible explanations are emerging.…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 99%
See 2 more Smart Citations